2010
DOI: 10.1002/adfm.200902347
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐Inspired Polydopamine Coating as a Universal Route to Hydroxyapatite Crystallization

Abstract: Bone tissue is a complex biocomposite material with a variety of organic (e.g., proteins, cells) and inorganic (e.g., hydroxyapatite crystals) components hierarchically organized with nano/microscale precision. Based on the understanding of such hierarchical organization of bone tissue and its unique mechanical properties, efforts are being made to mimic these organic–inorganic hybrid biocomposites. A key factor for the successful designing of complex, hybrid biomaterials is the facilitation and control of adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
537
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(577 citation statements)
references
References 41 publications
(24 reference statements)
21
537
0
1
Order By: Relevance
“…34 Then the PDA-modied surface can be used as a versatile platform for further reactions. [35][36][37] Recently, PDA-based synthesis of ZIF-8 and zeolite LTA membranes has been developed to improve their gas separation performance and reproducibility. [38][39][40] It can be expected, therefore, that ZIF-100 membranes prepared on PDA-functionalized supports will show higher gas separation performances and reproducibility of membrane preparation.…”
Section: Introductionmentioning
confidence: 99%
“…34 Then the PDA-modied surface can be used as a versatile platform for further reactions. [35][36][37] Recently, PDA-based synthesis of ZIF-8 and zeolite LTA membranes has been developed to improve their gas separation performance and reproducibility. [38][39][40] It can be expected, therefore, that ZIF-100 membranes prepared on PDA-functionalized supports will show higher gas separation performances and reproducibility of membrane preparation.…”
Section: Introductionmentioning
confidence: 99%
“…We have tested the stability of the CS shell by an ultrasonic shaking method described previously [30]. After 1 h of ultrasonic treatment, the CS shell was still present on the surface of the in situ 30CS -A microspheres and showed no evidence of delaminating from the microspheres (see the electronic supplementary material, figure S2), indicative of a high degree of stability.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a major focus of tissue engineering research is the design of bio-materials that provide information about cells and tissues. Inspired by mussel adhesion, scientists found that dopamine self-polymerized under alkaline conditions [63,65]. The reaction provides a universal coating for metals, polymers, and ceramics, regardless of their chemical and physical properties.…”
Section: Biomaterials Scaffoldsmentioning
confidence: 99%